HLA I immunopeptidome of synthetic long peptide pulsed human dendritic cells for therapeutic vaccine design - Amy L. Kessler; Roel F. A. Pieterman; Wouter A. S. Doff; Karel Bezstarosti; Rachid Bouzid; Kim Klarenaar; Diahann T. S. L. Jansen; Robbie J. Luijten; Jeroen A. A. Demmers; Sonja I. Buschow (npj Vaccines)
Abstract Synthetic long peptides (SLPs) are a promising vaccine modality that exploit dendritic cells (DC) to treat chronic infections or cancer. Currently, the design of SLPs relies on in silico prediction and multifactorial T cells assays to determine which SLPs are best cross-presented on DC human leukocyte antigen class I (HLA-I). Furthermore, it is unknown how TLR ligand-based adjuvants affect DC cross-presentation. Here, we generated a unique, high-quality immunopeptidome dataset of human DCs pulsed with 12 hepatitis B virus (HBV)-based SLPs combined with either a TLR1/2 (Amplivant®) or TLR3 (PolyI:C) ligand. The obtained immunopeptidome reflected adjuvant-induced differences, but no differences in cross-presentation of SLPs. We uncovered dominant (cross-)presentation on B-alleles, and identified 33 unique SLP-derived HLA-I peptides, several of which were not in silico predicted and some were consistently found across donors. Our work puts forward DC immunopeptidomics as a valuable tool for therapeutic vaccine design.